2012
DOI: 10.3390/v4123531
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Hepatitis C During Pregnancy and Childhood

Abstract: The worldwide prevalence of HCV infection is between 1% and 8% in pregnant women and between 0.05% and 5% in children. Yet the pathogenesis of hepatitis C during pregnancy and in the neonatal period remains poorly understood. Mother-to-child transmission (MTCT), a leading cause of pediatric HCV infection, takes place at a rate of <10%. Factors that increase the risk of MTCT include high maternal HCV viral load and coinfection with HIV-1 but, intriguingly, not breastfeeding and mode of delivery. Pharmacological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 135 publications
(169 reference statements)
0
56
0
8
Order By: Relevance
“…A literatura tem associado um aumento de até quatro vezes no risco de transmissão vertical da hepatite C em mulheres co-infectadas pelo HIV passando de 5,5 para 25%. 25,26 Quanto aos fatores de risco para apresentar infecção durante a gestação, na análise bivariada podemos observar que as mulheres solteiras tiveram um risco 2 vezes maior de apresentar alguma infecção durante o período gestacional do que as casadas. No entanto, após a análise ajustada esse achado desapareceu.…”
Section: Resultsunclassified
“…A literatura tem associado um aumento de até quatro vezes no risco de transmissão vertical da hepatite C em mulheres co-infectadas pelo HIV passando de 5,5 para 25%. 25,26 Quanto aos fatores de risco para apresentar infecção durante a gestação, na análise bivariada podemos observar que as mulheres solteiras tiveram um risco 2 vezes maior de apresentar alguma infecção durante o período gestacional do que as casadas. No entanto, após a análise ajustada esse achado desapareceu.…”
Section: Resultsunclassified
“…The pathophysiology of HCV during pregnancy is incompletely understood. During pregnancy, the maternal immune system must protect both the mother and the fetus from HCV infection while tolerating paternal alloantigens, thus avoiding immunological attack on fetal cells [9]. How this is accomplished is unclear.…”
Section: Vertical Transmissionmentioning
confidence: 99%
“…However, exposure to maternal blood can also occur with CS; accordingly, there is no reason to offer elective caesarean section to HCV-infected parturients [11][12][13][14] , with respect to special circumstances when CS is preferred to NVD, such as membranous rupture and internal fetal monitoring are confirmed to be associated with HCV transmission. CS and its complications were the main cause of death in many developing countries [15][16][17][18] . Egypt has the highest HCV prevalence worldwide; therefore, our results showed that the prevalence of HCV in a sample of Egyptian pregnant women was 2.08% (80 of 3,836 women), based on HCV Ab and PCR testing.…”
Section: Discussionmentioning
confidence: 99%